Vitamin B status in patients with type 2 diabetes mellitus with and without incipient nephropathy. Issue 1 (January 2015) - Nix, Wilfred A.; Zirwes, Rudolf; Bangert, Volkhard; Kaiser, Raimund Peter; Schilling, Matthias; Hostalek, Ulrike; Obeid, Rima
Abstract Aim To investigate the vitamin B status, with particular focus on vitamin B6, in adults with and without incipient nephropathy secondary to type 2 diabetes mellitus. Methods Plasma and/or urine concentrations of vitamins B6, B1, B12, related vitamers and biomarkers (including total homocysteine, methylmalonic acid) were measured in 120 adults with type 2 diabetes (including 46 patients with microalbuminuria) and 52 non-diabetic control subjects. Results Plasma concentrations of pyridoxal 5′-phosphate (PLP) were significantly lower in patients with type 2 diabetes than in control subjects (median: 22.7 nmol/L, diabetes with microalbuminuria; 26.8 nmol/L, diabetes without microalbuminuria; 39.5 nmol/L, non-diabetic control; p < 0.0001). The prevalence of low PLP (<30 nmol/L) was 63%, 58%, and 25% in the diabetes groups with and without microalbuminuria and the control group, respectively. Plasma levels of pyridoxine and pyridoxal were also lower (p < 0.0001), but levels of pyridoxamine, pyridoxamine 5′-phosphate, and pyridoxic acid were higher in both groups with diabetes compared to the control group (p < 0.001). Thiamine deficiency was highly prevalent in all groups, whereas low vitamin B12 and elevated methylmalonic acid were rare. Increased levels of C-reactive protein and soluble vascular cell adhesion molecule-1 were observed in the groups with diabetes (p < 0.05, versus healthy control). Conclusions Deficiency of vitamin B6 (PLP, pyridoxine, pyridoxal) and vitamin B1 (thiamine) was prevalent in type 2 diabetes. Incipient nephropathy was associated with more pronounced alterations in vitamin B6 metabolism and stronger indications of endothelial dysfunction and inflammation.